Between the local and the global? : reindeer herders’ perspectives on land use challenges and conflicts in the Sámi homeland, Finland - Turunen, Minna T; Rikkonen, Taru; Nikula, Ari; Tuulentie, Seija; Rautio, Pasi (Journal of Land Use Science)
Rapid increase in new land uses is one of the biggest threats to reindeer husbandry in Fennoscandia. We conducted a partly facilitated online Public Participation GIS survey to study reindeer herders’ perspectives on the impacts of land uses on reindeer herding in Inari, in the Sámi Homeland, Finland. The herders found that predators, husky safaris, hunting, mineral prospecting, gold mining, and forestry have had the most negative influence on reindeer herding, but they were most concerned about the cumulative effects of multiple land uses. Nature conservation was reported as having the most positive impact on reindeer herding. Map markings of the herders indicated that new land uses should not be directed to grazing areas but to population centers with existing infrastructure. The facilitated PPGIS survey encompassing interviews was found to be time-consuming, but trust-inspiring and interactive in that it enabled detailed discussions with the herders. 2024